Direct-Acting Oral Anticoagulants in patients at extremes of body weight: a review of pharmacological considerations and clinical implications - Talerico, Rosa; Pola, Roberto; Klok, Frederikus Albertus; Huisman, Menno Volkert (TH Open, 2024)
Patients at extremes of body weight are underrepresented in randomized controlled trials of direct-acting oral anticoagulants (DOACs). Therefore, their optimal anticoagulant treatment remains a topic of debate.The aim of this narrative review is to summarize the evidence on the pharmacokinetic and pharmacodynamic profile of DOACs for treating patients at extremes of body weight in venous thromboembolism (VTE) and in the prevention of cardioembolic stroke in nonvalvular atrial fibrillation (NVAF). A literature search was conducted in the main bibliographic databases, and the most relevant reviews and original articles on the topic were selected.Although data in these patient groups are limited, apixaban and rivaroxaban show a favorable pharmacokinetic and pharmacodynamic profile in obese VTE treatment and NVAF patients and, in the case of apixaban, also in underweight patients. In particular, these drugs demonstrated comparable efficacy and safety to standard therapy. Very few data were available for dabigatran and edoxaban; the latter drug was safer at a lower dose, mainly in underweight patients.Our findings are in line with the last International Society of Haemostasis and Thrombosis position paper and European Heart Rhythm Association 2021 practical guide, suggesting the use of apixaban and rivaroxaban in morbidly obese patients (>120 kg or body mass index ≥40 kg/m2) and the reduced dosage of edoxaban in low-weight patients. Future studies should focus on large populations of patients at extremes of body weights to acquire more clinical and pharmacokinetic evidence on all available DOACs, especially those currently less investigated.
Keywords: direct-acting oral anticoagulants; obese; underweight; extremes of body weight; pharmacokinetics